Theories to Guide Children Development and Their Impact on Early Childhood Education - Al-Harbi, Salwa Saeed (Journal of Ecohumanism, 2024)
The mind of a child is complex. A number of developmental theories help educators understand this complexity in order to better deal with it and guide the child’s development. Many theorists have been influential to the child development and education fields. The various theorists in child development have come up with ideas and innovative ways to work with and understand the development process of children. The developmental theories of the past and also the emerging theories encompass cognitive, social, physical, and other aspects of human development which are represented as stages or focus on a specific area (Woolfolk & Perry, 2012). This article describes the theories of development and its greatest impact on early childhood development education. This article also discusses such as theories, and theoretical concepts. it focuses on six theories which are behavioral child development theories, Psycho-social theory, Piaget's cognitive developmental theory, Vygotsky's sociocultural theory, Bronfenbrenner’s Ecological systems theory, and Kohlberg's moral development theory. The article concludes with some recommendations for parents and educators.